Applications of contemporary imaging modalities in orthodontics - Cesur, Emre; Orhan, Kaan (Ondokuz Mayıs Üniversitesi, 2021)
The validity of orthodontic diagnosis and treatment planning depends on the accuracy of the photos, models and radiograps to be obtained from the patient. One of the most important parts of diagnosis and treatment planning is the use of appropriate imaging method. Although lateral cephalometric radiographs are still the most preferred imaging method, other methods such as hand-wrist radiographs, panoramic radiographs, cone beam computerized tomography (CBCT), magnetic resonance imaging (MRI), and ultrasound are also frequently used. For this reason, it is important to know the advantages and disadvantages of all imaging methods for orthodontists in order to select the most suitable method for the patient. Although 2D imaging modalities are still frequently preferred in terms of their accessibility, CBCT use may come to the fore when precise imaging of hard tissues is desired. In cases where TMJ region and soft tissues are to be imaged, the use of MRI and ultrasound should be considered. Orthodontists should follow up the up-to-date usage areas of the developing imaging methods.
Keywords: 3D Imaging; CBCT; Contemporary Imaging; Digital Imaging; Orthodontics